Collagen hydrogel loaded with gold nanoclusters, preparation method and application
By the hydrogel formed by the cross -linked collagen -modified collagen -modified collagen -modified collagen -modified collagen -modified collagen in the intellectual hydraulic gel that targets the II collagen. The precise targeted and efficient anti -inflammatory and cartilage regeneration effects of cartilage tissue.
Patent Information
- Application Number
- CN202410622188.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-20
- Publication Date
- 2025-01-28
AI Technical Summary
The existing gold nanoclusters are quickly cleared in the human body, have short residence time, and lack precise target recognition capabilities, which leads to huge challenges in disease treatment.
By combining the hydraulic gel (CSH-AUNCS-CIITP) formed by the Auncs-CIITP that targets the functionalization of polypeptides with the mellastin (COL I-SH) combined , Realize the anti -inflammatory and cartilage regeneration effects of the controlled release and accurately targeting cartilage tissue.
The hydrogel has excellent biocompatibility and biological activity, can significantly promote cell proliferation and cartilage differentiation, achieve intelligent response to high-level activated oxygen and the controllable release of Auncs-CIITP, significantly improve the anti-inflammatory and cartilage regeneration efficiency.
Smart Images

Figure CN119367265A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a collagen hydrogel loaded with gold nanoclusters, a preparation method and an application thereof. Background Art
[0002] Osteoarthritis (OA) is a widespread degenerative joint disease that affects the health and quality of life of approximately 500 million people worldwide. OA patients not only suffer from physical pain and impaired function, but may also face the risk of disability. The pathogenesis of OA is complex and mainly manifested as chronic inflammation and cartilage degeneration. Studies have shown that the level of reactive oxygen species (ROS) in the cartilage of OA patients is significantly increased, pro-inflammatory factors are upregulated, and ultimately lead to degradation of the cartilage extracellular matrix.
[0003] Clinical treatments for OA include physical intervention, drug therapy, and surgical treatment. At present, drug intervention is still the main method for clinical treatment of OA. For example, oral nonsteroidal anti-inflammatory drugs (NSAIDs), cyclooxygenase-2 (COX-2) inhibitors, and acetaminophen can relieve pain and improve function, but the emergence of drug resistance affects their application. In addition, intra-articular injection of corticosteroids, hyaluronic acid, platelet-rich plasma, glucosamine, or chondroitin can improve the local bioavailability of drugs and relieve symptoms, but the local nature limits their clinical application.
[0004] Inorganic nanoparticles have attracted much attention in the treatment of OA due to their precisely adjustable size and unique biochemical properties. Gold nanoparticles (AuNPs) have been used to treat OA due to their good anti-inflammatory properties. However, the high toxicity and poor stability of gold nanoparticles limit their clinical application. In recent years, gold nanoclusters (AuNCs) have been expected to replace AuNPs and be used in the treatment of inflammatory-related diseases due to their ultra-small size, good stability, excellent biocompatibility and inherent bioactivity. However, AuNCs have a fast clearance rate and short residence time in the human body, and lack accurate target recognition capabilities, so they face great challenges in the efficient treatment of diseases.
[0005] The inventor unexpectedly discovered that AuNCs not only have anti-inflammatory effects, but also promote cartilage tissue regeneration; type II collagen targeted polypeptide functionalized gold nanoclusters (AuNCs-CIITP) can accurately target cartilage tissue, thereby improving the efficiency of anti-inflammatory and cartilage regeneration; thiol-modified type I collagen (Col I-SH) can form a hydrogel (CSH) through cross-linking and serve as a carrier of AuNCs-CIITP to achieve controlled release. CSH-AuNCs-CIITP hydrogel has low swelling and resistance to enzyme degradation, as well as good mechanical properties and injectability; the hydrogel has excellent biocompatibility and bioactivity, and can significantly promote cell proliferation and chondrogenic differentiation of bone marrow mesenchymal stem cells; CSH-AuNCs-CIITP hydrogel can intelligently respond to high levels of reactive oxygen species, controllably release AuNCs-CIITP, and target recognition of cartilage matrix, thereby achieving anti-inflammatory and cartilage regeneration functions; the hydrogel provides broad prospects for the precise treatment of OA with complex pathology. Summary of the invention
[0006] In view of the above technical problems, the object of the present invention is to provide a collagen hydrogel loaded with gold nanoclusters, wherein the hydrogel is collagen encapsulating gold nanoclusters, and the gold nanoclusters are connected to targeting polypeptides.
[0007] Preferably, the collagen is yak collagen.
[0008] Preferably, the yak collagen is thiol-modified yak type I collagen, type II and / or type III collagen.
[0009] Preferably, the targeting polypeptide is a type II collagen targeting polypeptide.
[0010] The second object of the present invention is to provide a method for preparing the collagen hydrogel loaded with gold nanoclusters, comprising the following steps:
[0011] (1) At room temperature, a tetrachloroauric acid tetrahydrate solution, a targeting polypeptide aqueous solution and a glutathione solution are mixed, stirred evenly at 25° C., heated to 70° C., and stirred continuously in a dark environment; 75% ethanol is added for purification, centrifuged, and dried to obtain gold nanoclusters functionalized with the targeting polypeptide;
[0012] (2) Dissolving collagen in acetic acid solution and adjusting the pH to 8.0; adding PBS buffer solution, EDTA and DL-N-acetylhomocysteine thiolactone; stirring at room temperature under nitrogen protection, adding dihexathreitol, continuing stirring, dialyzing, freeze-drying, dissolving in acetic acid solution, stirring, and dialyzing to neutrality to obtain thiol-modified collagen;
[0013] (3) The gold nanoclusters functionalized with the targeted polypeptide obtained in step (1) and the thiol-modified collagen obtained in step (2) are quickly mixed at a mass ratio of 1:9 and placed at room temperature to form a collagen hydrogel loaded with gold nanoclusters.
[0014] Preferably, the volume ratio of the targeting polypeptide aqueous solution to the glutathione solution in step (1) is 1:9.
[0015] Preferably, the pH is adjusted in step (2) using 1M NaOH solution.
[0016] The third object of the present invention is to provide the use of the collagen hydrogel loaded with gold nanoclusters in the preparation of products promoting bone / cartilage tissue regeneration.
[0017] The fourth object of the present invention is to provide the use of the collagen hydrogel loaded with gold nanoclusters in the preparation of drugs for preventing and / or treating cartilage defects and arthritis.
[0018] Preferably, the arthritis is infectious arthritis and / or non-infectious arthritis.
[0019] Preferably, the non-infectious arthritis includes one or more of degenerative arthritis, rheumatoid arthritis, gouty arthritis and osteoarthritis.
[0020] The beneficial effects of the present invention are as follows: (1) the present invention provides a collagen hydrogel loaded with gold nanoclusters, wherein the hydrogel is collagen encapsulating gold nanoclusters, and the gold nanoclusters are connected with targeting polypeptides; the gold nanoclusters not only have anti-inflammatory effects, but also can promote cartilage tissue regeneration; gold nanoclusters functionalized with type II collagen targeting polypeptides (AuNCs-CIITP) can accurately target cartilage tissue, thereby improving the efficiency of anti-inflammatory and cartilage regeneration; thiol-modified type I collagen (Col I-SH) can form a hydrogel (CSH) by cross-linking, and can be used as a carrier of AuNCs-CIITP to achieve controlled release;
[0021] (2) The hydrogel (CSH-AuNCs-CIITP) has low swelling and resistance to enzyme degradation, as well as good mechanical strength and injectability;
[0022] (3) The hydrogel (CSH-AuNCs-CIITP) has excellent biocompatibility and bioactivity, and can significantly promote cell proliferation and chondrogenic differentiation of bone marrow mesenchymal stem cells;
[0023] (4) The hydrogel (CSH-AuNCs-CIITP) can intelligently respond to high levels of reactive oxygen species and achieve controlled release of AuNCs-CIITP. The released AuNCs-CIITP can target cartilage tissue and achieve anti-inflammation and cartilage regeneration, and is used in the treatment of osteoarthritis. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Physicochemical characterization of AuNCs-CIITP
[0025] Note: A is the UV and fluorescence spectra of AuNCs-CIITP;
[0026] B is the TEM image of AuNCs-CIITP;
[0027] C is the fluorescence intensity of AuNCs and AuNCs-CIITP on type II collagen-coated plates;
[0028] D is the Zeta potential of CIITP, AuNCs and AuNCs-CIITP.
[0029] Figure 2 Physicochemical characterization of CSH-AuNCs-CIITP hydrogel
[0030] Note: A is the photo of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels;
[0031] B is the SEM images of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels;
[0032] C is the swelling properties of Col-AuNCs-CIITP, CSH, and CSH-AuNCs-CIITP hydrogels;
[0033] D is the enzymatic degradation characteristics of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels.
[0034] Figure 3 Mechanical and injectable properties of CSH-AuNCs-CIITP hydrogels Note: A is the compression modulus of Col-AuNCs-CIITP, CSH, and CSH-AuNCs-CIITP hydrogels;
[0035] B is the frequency-dependent oscillatory shear rheology test of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels; C is the continuous step strain test of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels;
[0036] D is the injectability of CSH-AuNCs-CIITP hydrogel.
[0037] Figure 4 ROS response and nanoparticle release of CSH-AuNCs-CIITP Note: A shows the morphological changes of CSH-AuNCs-CIITP hydrogel in PBS and 0.1 mM H2O2;
[0038] B is the cumulative release of Col-AuNCs-CIITP and CSH-AuNCs-CIITP hydrogels in PBS;
[0039] C is the cumulative release of CSH-AuNCs-CIITP hydrogel in PBS, 0.1 mM H2O2, and 0.5 mM H2O2;
[0040] D is the nanoparticle release from CSH-AuNCs-CIITP hydrogel stimulated by PBS and 0.1 mM H2O2 cycles.
[0041] Figure 5 Cytotoxicity and proliferation of CSH-AuNCs-CIITP hydrogels
[0042] Note: A is the in vitro cytotoxicity of AuNCs-CIITP;
[0043] B is the CCK-8 assay of bone marrow mesenchymal stem cells (BMSCs) co-cultured with AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP;
[0044] C is the live / dead cell staining image of BMSCs co-cultured with AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP.
[0045] Figure 6 Cell adhesion and chondrogenic differentiation of CSH-AuNCs-CIITP hydrogels Note: A is the immunofluorescence staining of BMSCs co-cultured with AuNCs-CIITP, Col-AuNCs-CIITP, and CSH-AuNCs-CIITP;
[0046] B is the relative expression level of Acan gene in BMSCs co-cultured with AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP;
[0047] C is the relative expression level of Col2a1 gene in BMSCs co-cultured with AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP;
[0048] D is the relative expression level of Sox9 gene in BMSCs co-cultured with AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP.
[0049] Figure 7 Cartilage tissue regeneration at 8 weeks after CSH-AuNCs-CIITP hydrogel implantation into the defect Note: A is the apparent image of AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP, and CSH-AuNCs-CIITP groups;
[0050] B is the macrohistological scores of AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP groups; C is the H&E tissue staining image of AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP groups; D is the Masson tissue staining image of AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP groups; E is the Saf-O / FG tissue staining image of AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP groups.
[0051] Figure 8 Sirius red staining after CSH-AuNCs-CIITP hydrogel repaired rat cartilage defects. Notes: A is the Sirius red tissue staining of AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP groups;
[0052] B is the orientation distribution of collagen fibers in the surface (upper 1 / 3) and basal (lower 2 / 3) regions of the Sirius red staining images of the AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP, and CSH-AuNCs-CIITP groups;
[0053] C is the polar coordinates of collagen fiber orientation in the surface and basal regions of the picrosirius red staining images of the AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP, and CSH-AuNCs-CIITP groups. DETAILED DESCRIPTION
[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] It should be noted that the reagents used in the following examples, unless otherwise specified, can be purchased from the market.
[0056] In the following examples, it should be noted that AuNCs is the abbreviation of gold nanoclusters; CIITP is the abbreviation of type II collagen targeting polypeptide; AuNCs-CIITP is the abbreviation of gold nanoclusters functionalized with type II collagen targeting polypeptide; CSH-AuNCs-CIITP is the abbreviation of collagen hydrogel loaded with gold nanoclusters functionalized with type II collagen targeting polypeptide; Col I-SH is the abbreviation of type I collagen modified with thiol. In some examples and drawings of the specification, the abbreviations are directly used instead of the full names, which have the same meaning.
[0057] Example 1 Preparation of AuNCs
[0058] 100 mL of 20 mM tetrachloroauric acid tetrahydrate (HAuCl4·4H2O) solution and 100 mL of 30 mM glutathione solution were added to a round-bottom flask, stirred evenly at 25°C, then heated to 70°C and stirred for 24 hours in a dark environment; then, 75% ethanol was added to the formed yellow solution for purification; finally, gold nanoclusters (AuNCs) were obtained by centrifugation and drying.
[0059] Example 2 Preparation of AuNCs-CIITP
[0060] 100 mL of 20 mM tetrachloroauric acid tetrahydrate (HAuCl4·4H2O) solution, 10 mL of 30 mM CIITP aqueous solution and 90 mL of 30 mM glutathione solution were added to a round-bottom flask, stirred evenly at 25 °C, then heated to 70 °C and stirred for 24 hours in a dark environment; then, 75% ethanol was added to the formed yellow solution for purification; finally, AuNCs-CIITP was obtained by centrifugation and drying.
[0061] Example 3 Preparation of Col I-SH
[0062] 250 mg of type I collagen was dissolved in 50 mL of 0.3 M acetic acid solution, and the pH was adjusted to 8.0 with 1 M NaOH solution; then, 0.2 M sodium dihydrogen phosphate-sodium dihydrogen phosphate (PBS) buffer solution, 0.01 g of EDTA and 200 mg of DL-N-acetylhomocysteine thiolactone (AHCT) were added; under nitrogen protection, the mixture was stirred at room temperature for 24 hours, 200 mg of dihexathreitol (DTT) was added, and stirring was continued for 12 hours; finally, after dialysis and freeze-drying, Col I-SH was obtained.
[0063] Example 4 Preparation of CSH-AuNCs-CIITP hydrogel
[0064] Col I-SH was dissolved in 0.3 M acetic acid solution to form a uniform solution with a concentration of 5 mg / mL, and then dialyzed to neutrality by gradient dialysis. Subsequently, 100 μL of 5 mg / mL AuNCs-CIITP aqueous solution was quickly mixed with 900 μL of Col I-SH solution and allowed to stand at room temperature for 4 hours to form CSH-AuNCs-CIITP hydrogel. Figure 2 As shown in A.
[0065] Example 5 Preparation of CSH hydrogel
[0066] Col I-SH was dissolved in 0.3 M acetic acid solution to form a uniform solution with a concentration of 5 mg / mL, and then dialyzed to neutralize it; then, it was left to stand at room temperature for 4 hours to form a thiol-crosslinked collagen (CSH) hydrogel. Figure 2 As shown in A.
[0067] Example 6 Preparation of Col-AuNCs-CIITP hydrogel
[0068] Type I collagen (Col I) was dissolved in 0.3 M acetic acid solution to form a uniform solution with a concentration of 5 mg / mL, and then gradient dialyzed to make it neutral; then, 100 μL of 5 mg / mL AuNCs-CIITP aqueous solution was quickly mixed with 900 μL of Col I solution and left to stand at room temperature for 4 hours to form Col-AuNCs-CIITP hydrogel. Figure 2 As shown in A.
[0069] Example 7 Characterization of AuNCs-CIITP
[0070] (1) The AuNCs-CIITP prepared in Example 2 was dissolved to form a uniform aqueous solution with a concentration of 5 mg / mL, and then measured by UV-visible absorption spectroscopy and fluorescence luminescence spectroscopy.
[0071] The results are as follows Figure 1 As shown in A, the UV-visible spectrum of AuNCs-CTP shows a characteristic absorption peak at a wavelength of 415 nm, while its fluorescence spectrum shows an obvious emission peak at a wavelength of 610 nm. At the same time, under visible light, the AuNCs-CIITP solution appears light yellow, and under ultraviolet light with a wavelength of 415 nm, it exhibits red fluorescence. The results indicate the successful synthesis of AuNCs-CIITP.
[0072] (2) The AuNCs-CIITP prepared in Example 2 was dispersed in an aqueous solution, then dropped onto a copper grid and air-dried, and its nanostructure was characterized using a transmission electron microscope (TEM) at a voltage of 200 kV.
[0073] The results of transmission electron microscopy are as follows Figure 1 As shown in Figure B, the results show that AuNCs-CIITP has ultra-small size and good dispersion. The results further indicate the successful synthesis of AuNCs-CIITP.
[0074] (3) A 0.2 mg / mL type II collagen solution was prepared using phosphate buffered saline (PBS, pH 7.4). 100 μL of the type II collagen solution was added to a black flat-bottom 96-well microplate and incubated overnight at 4°C. The plate was blocked with a 2% BSA solution at room temperature for 1 hour, followed by three rinses with 1× PBS. 100 μL of AuNCs or AuNCs-CIITP (0.5 mg / mL) was added to each well. The plate was gently shaken and incubated for 4 hours at room temperature, followed by three rinses with 1× PBS. 100 μL of DMSO was added to each well to dissolve the residual nanoparticles. Finally, the fluorescence intensity was measured using an ELISA reader.
[0075] The results are as follows Figure 1 As shown in Figure C, the results show that the fluorescence intensity of the AuNCs-CIITP group is significantly higher than that of the AuNCs group. The results show that the type II collagen targeting peptide is successfully bound to AuNCs-CIITP.
[0076] (4) The AuNCs and AuNCs-CIITP prepared in Examples 1 and 2 were dispersed in an aqueous solution and then added to a sample cell. The surface Zeta potential was measured using a Malvern ZEN 3600 Zetasizer dynamic light scattering (DLS) method.
[0077] The results are as follows Figure 1As shown in Figure D, the Zeta potential of AuNCs was initially negative, the Zeta potential of CIITP was initially positive, and the Zeta potential of AuNCs-CIITP was between AuNCs and CIITP. The results further showed that CIITP successfully functionalized AuNCs to form AuNCs-CIITP.
[0078] Example 8 Physicochemical Characterization of CSH-AuNCs-CIITP Hydrogel
[0079] (1) The CSH-AuNCs-CIITP, CSH and Col-AuNCs-CIITP hydrogels prepared in Examples 4-6 were freeze-dried and then fixed on a sample stage. After gold spraying for 25 seconds, the sample morphology was detected using a scanning electron microscope (SEM) at a voltage of 5.0 kV.
[0080] The results of scanning electron microscopy are as follows Figure 2 B shows the SEM images of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP from left to right. The results show that Col-AuNCs-CIITP hydrogel shows unevenly distributed smaller pores, while porous network structures with relatively large pores and ordered structures are observed in CSH and CSH-AuNCs-CIITP hydrogels. The results show that CSH-AuNCs-CIITP hydrogel has a good nanoporous structure.
[0081] (2) The CSH-AuNCs-CIITP, CSH and Col-AuNCs-CIITP hydrogels prepared in Examples 4-6 were freeze-dried and weighed (m0, g), and then completely immersed in an equal volume of PBS solution. Subsequently, after extraction from the PBS solution at specific time points and removal of excess surface water, the sample weight was re-weighed (m t , g). The calculation formula of swelling ratio (SR) is SR (g / g) = (m t -m0) / m0.
[0082] The results are as follows Figure 2 As shown in Figure C, the swelling ratio (SR) of Col-AuNCs-CIITP gradually increased and reached equilibrium after 12 hours, with a value as high as 125.7; in contrast, the equilibrium SR of CSH and CSH-AuNCs-CIITP decreased significantly to 37.4 and 32.0, respectively, within 12 hours. The results show that CSH-AuNCs-CIITP hydrogel has a smaller swelling property.
[0083] (3) The CSH-AuNCs-CIITP, CSH and Col-AuNCs-CIITP hydrogels prepared in Examples 4-6 were freeze-dried and accurately weighed (m0, mg). The freeze-dried hydrogel samples were completely immersed in a collagenase solution with a concentration of 10 U / mL and incubated at 37°C. At specific time points, the samples were removed from the collagenase solution and rinsed three times with deionized water. After freeze-drying, the residual samples were weighed (m t The calculation formula of the mass degradation percentage (MD, %) of the sample is: MD (%) = (m0-m t ) / m0×100%.
[0084] The results are as follows Figure 2 As shown in D, Col-AuNCs-CIITP reached equilibrium in only 48 hours, with a degradation rate of 96.7%; however, CSH and CSH-AuNCs-CIITP reached equilibrium after 7 days, with relatively low degradation rates of 80.9% and 77.5%, respectively. The results show that CSH-AuNCs-CIITP hydrogel has significant resistance to enzyme degradation.
[0085] Example 9 Mechanical properties and injectability of CSH-AuNCs-CIITP hydrogel
[0086] (1) CSH-AuNCs-CIITP, CSH and Col-AuNCs-CIITP hydrogels with a diameter of 16 mm and a thickness of 4 mm were prepared in a mold according to the method of Examples 4-6, and then subjected to a compression test at a speed of 5% strain / min.
[0087] The results are as follows Figure 3 As shown in A, the compression moduli of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels are 13.4 kPa, 72.1 kPa and 88.6 kPa, respectively. The results show that CSH-AuNCs-CIITP hydrogel has excellent mechanical strength.
[0088] (2) CSH-AuNCs-CIITP, CSH and Col-AuNCs-CIITP hydrogels were prepared according to Examples 4-6, and their rheological behaviors as a function of frequency were measured under a fixed strain (1%).
[0089] The results are as follows Figure 3As shown in B, the frequency-dependent oscillatory shear rheology shows that the G' value is dominant, and the G' values of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels are approximately 51.9 Pa, 947.3 Pa and 1100.7 Pa, respectively. The results show that the mechanical strength of CSH-AuNCs-CIITP hydrogel is significantly increased compared with Col-AuNCs-CIITP and CSH hydrogels.
[0090] (3) CSH-AuNCs-CIITP, CSH and Col-AuNCs-CIITP hydrogels were prepared according to Examples 4-6, and then dynamic step strain measurements were performed at a low strain of γ = 1.0% and a high strain of γ = 300%.
[0091] The results are as follows Figure 3 As shown in Figure C, the networks of Col-AuNCs-CIITP, CSH and CSH-AuNCs-CIITP hydrogels were rapidly destroyed under high strain (300%), causing G' to decrease to about 2.4Pa, 63.9Pa and 80.8Pa, respectively; under low strain (1%) conditions, G' and G" of all three hydrogels were almost completely recovered in a short time. The results show that CSH-AuNCs-CIITP hydrogel has excellent self-healing ability.
[0092] (4) CSH-AuNCs-CIITP hydrogel was prepared according to Example 4, and then placed in a 1 mL syringe and extruded into a glass culture dish.
[0093] The results are as follows Figure 3 As shown in D, CSH-AuNCs-CIITP hydrogel can be uniformly and continuously extruded from the injection. In addition, the hydrogel can be injected to form recognizable patterns such as "GAu" and "CTP". The results show that CSH-AuNCs-CIITP hydrogel has good injectable properties.
[0094] Example 10 ROS response and nanoparticle release of CSH-AuNCs-CIITP hydrogel
[0095] (1) CSH-AuNCs-CIITP hydrogels were prepared according to Example 4 and completely immersed in PBS solution (pH 7.4) and 0.1 mM H2O2 solution. The morphology of the hydrogels was observed and photographed on days 0, 4, and 7, respectively.
[0096] The results are as follows Figure 4As shown in A, the hydrogel still exists obviously after being immersed in PBS solution for 7 days, while the hydrogel immersed in H2O2 solution is almost completely degraded. The results show that CSH-AuNCs-CIITP hydrogel exhibits smart ROS response performance.
[0097] (2) CSH-AuNCs-CIITP and Col-AuNCs-CIITP hydrogels were prepared according to Examples 4 and 6, encapsulated in dialysis bags (8-10 kDa), and immersed in PBS solutions with a volume ratio of 1:20, respectively. They were then placed in an oscillator at 37°C for incubation. At each time point, the fluorescence intensity of the PBS solution was measured using a fluorescence spectrophotometer, and the relative concentration of the released gold nanoclusters was calculated by the ratio of the absorbance.
[0098] The results are as follows Figure 4 As shown in Figure B, the Col-AuNCs-CIITP hydrogel almost completely released AuNCs-CIITP within 2 days, while the CSH-AuNCs-CIITP hydrogel showed an S-shaped release curve with a slower release rate, releasing 75.45% within 7 days. The results show that the CSH-AuNCs-CIITP hydrogel can achieve sustained release of AuNCs-CIITP.
[0099] (3) CSH-AuNCs-CIITP hydrogels were prepared according to Examples 4 and 6, and encapsulated in dialysis bags (8-10 kDa) and immersed in PBS solution, 0.1 mM H2O2, and 0.5 mM H2O2 solutions, respectively. At each time point, the release of gold nanoclusters from CSH-AuNCs-CIITP hydrogels was evaluated using a fluorescence spectrophotometer.
[0100] The results are as follows Figure 4 As shown in Figure C, the release rate of AuNCs-CIITP in CSH-AuNCs-CIITP hydrogel increases with the increase of H2O2 concentration. After 48 hours, the release rates in PBS solution, 0.1mM H2O2 and 0.5mM H2O2 solution were 43.2%, 72.5% and 94.1%, respectively. The results show that CSH-AuNCs-CIITP hydrogel can intelligently respond to ROS and achieve controllable release of AuNCs-CIITP.
[0101] (4) CSH-AuNCs-CIITP hydrogel was prepared according to Example 4. PBS and 0.1 mM H2O2 solution were used to stimulate the CSH-AuNCs-CIITP hydrogel in an alternating cycle every two hours. Finally, the content of gold nanoclusters in the solution was measured.
[0102] The results are as follows Figure 4As shown in D, CSH-AuNCs-CIITP hydrogels showed similar AuNCs-CIITP release curves within three and a half cycles. The results showed that CSH-AuNCs-CIITP hydrogels can achieve stable ROS response and release of gold nanoclusters.
[0103] Example 11 Cytotoxicity and proliferation of CSH-AuNCs-CIITP hydrogel
[0104] (1) Trypsin was used to digest the adherent BMSCs, and then α-MEM complete medium was added to dilute them to a density of 2×10 5 cells / mL of cell suspension. 100 μL of BMSCs suspension containing different concentrations of AuNCs-CIITP was added to each well of a 96-well plate and cultured in an incubator for 24 hours. The culture medium was removed and 100 μL of 10% CCK-8 solution was added to each well. After incubation at 37°C for 1 hour, the absorbance at 450 nm was measured using a microplate reader.
[0105] The results are as follows Figure 5 As shown in A, when AuNCs-CIITP was co-cultured with BMSCs in the concentration gradient range of 0.01 to 1 mg / mL, the cell viability of BMSCs was always close to 100%. The results showed that AuNCs-CIITP had no cytotoxicity.
[0106] (2) 100 μL of cell suspension containing AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP was added to a 96-well plate and cultured for 1, 4 and 7 days, respectively. The culture medium was removed and 100 μL of 10% CCK-8 solution was added to each well. After incubation at 37°C for 1 hour, the absorbance at 450 nm was measured using a microplate reader.
[0107] The results are as follows Figure 5 As shown in B, the cell viability of AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP groups increased in a time-dependent manner from 1 to 7 days. Compared with the Blank group, the number of surviving cells in AuNCs-CIITP increased significantly; compared with AuNCs-CIITP and Col-AuNCs-CIITP, the number of cells in CSH-AuNCs-CIITP increased significantly. The results showed that CSH-AuNCs-CIITP could significantly promote cell proliferation.
[0108] (3) AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP were mixed with BMSCs cells to form a density of 1×10 5cells / mL suspension. These mixtures were then added to laser confocal culture dishes and cultured for 4 and 7 days. At each time point, calcein-AM and propidium iodide in the live / dead cell staining kit were used to stain live and dead cells, respectively. Finally, images were collected using a laser confocal microscope.
[0109] The results are as follows Figure 5 As shown in Figure C, after 7 days of culture, the proportion of surviving cells in CSH-AuNCs-CIITP hydrogel was significantly the highest. The results showed that CSH-AuNCs-CIITP hydrogel significantly enhanced the ability of cell proliferation by controlling the release of AuNCs-CIITP.
[0110] Example 12 Cell Adhesion and Chondrogenic Differentiation of CSH-AuNCs-CIITP Hydrogel
[0111] (1) 1 mL of cell suspension containing AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP was added to a laser confocal microscopy dish, and after culturing in an incubator for 4 days, BMSCs were fixed with 4% paraformaldehyde for 15 minutes, permeabilized with 0.1% Triton X-100 for 5 minutes, and blocked with 1% BSA solution at room temperature for 30 minutes. After staining the cells with phosphatidylcholine-tetramethylrhodamine isothiocyanate and Hoechst 33342, fluorescence images were obtained using a laser confocal microscope.
[0112] The results are as follows Figure 6 As shown in A, the cytoskeleton structure of cells in the Blank group and AuNCs-CIITP group was poor, and the number of BMSCs was relatively limited; Col-AuNCs-CIITP hydrogel adhered more cells with developed cytoskeleton structure; the number of BMSCs adhered to CSH-AuNCs-CIITP hydrogel increased significantly, and presented a beautiful actin cytoskeleton structure. The results show that CSH-AuNCs-CIITP hydrogel effectively promotes the adhesion of BMSCs.
[0113] (2) BMSCs were mixed with AuNCs-CIITP, Col-AuNCs-CIITP and CSH-AuNCs-CIITP to form a 1×10 5cells / mL suspension and incubated in 6-well plates for 3 and 7 days, respectively. Total RNA was extracted from cells using an RNA isolation kit. The concentration and purity of RNA samples were determined using a NanoDrop spectrophotometer. cDNA was synthesized using a PrimeScriptRTreagent Kit and gDNAEraser, and gene expression levels were analyzed using TB Green Premix Ex Taq II. The expression of cartilage-specific genes was detected using a Real-Time PCR System. 2 -ΔΔCT The relative expression of the target gene was calculated by the method and normalized to the expression level of β-actin.
[0114] The results are as follows Figure 6 As shown in BD, after 7 days of co-culture with cells, the gene expression levels of Acan, Col2a1 and Sox9 in the AuNCs-CIITP group increased significantly by 4.3 times, 3.2 times and 2.6 times, respectively, indicating that AuNCs-CIITP can effectively promote the chondrogenic differentiation of BMSCs. The expression levels of the three genes in the CSH-AuNCs-CIITP group increased by 7.0 times, 5.0 times and 4.6 times, respectively, which were significantly higher than those in the Col-AuNCs-CIITP group. The results show that the CSH-AuNCs-CIITP hydrogel has excellent biological activity.
[0115] Example 13 Cartilage tissue regeneration by CSH-AuNCs-CIITP
[0116] (1) SD rats (male, 250-300 g) were housed in a standard laboratory. Fifteen rats were randomly divided into five groups (Blank group, AuNCs group, AuNCs-CIITP group, Col-AuNCs-CIITP group, and CSH-AuNCs-CIITP group), with 3 rats in each group. Before surgery, the rats were anesthetized by intraperitoneal injection of 10% (w / v) sodium pentobarbital (0.3 mL / 100 g). After shaving and disinfecting the surgical site, the skin and muscle tissue covering the left knee of each rat were incised with a scalpel to expose the joint pulley site. A cylindrical cartilage defect with a diameter of 2 mm and a height of 1.5 mm was formed at the pulley site of the left knee of each rat using an electric drill. Subsequently, AuNCs, AuNCs-CIITP, Col-AuNCs-CIITP, and CSH-AuNCs-CIITP samples were injected into the surgical site to completely fill the defect, except for the Blank group. After 8 weeks, the rats in each group were euthanized using an overdose of sodium pentobarbital, and the samples were collected.
[0117] The experimental results are as follows Figure 7As shown in AB, at 8 weeks after surgery, the AuNCs-CIITP group showed significant cartilage defect repair effects compared with the Blank group and AuNCs. The CSH-AuNCs-CIITP group showed the best cartilage defect repair effect, with a smooth surface of the new cartilage tissue and seamless integration with the surrounding host tissue. The ICRS macroscopic score showed that the CSH-AuNCs-CIITP group had significant cartilage regeneration ability at 8 weeks compared with the Blank, AuNCs, AuNCs-CIITP, and Col-AuNCs-CIITP groups, which was consistent with the results of gross morphological observations.
[0118] (2) The collected specimens were fixed in 4% formaldehyde for 2 days and decalcified with 10% ethylenediaminetetraacetic acid (EDTA) solution for 7 days. Subsequently, the samples were dehydrated in alcohol gradients, embedded in paraffin, and cut into 6 μm slices. Finally, the tissue sections were stained with hematoxylin & eosin (H&E).
[0119] The experimental results are as follows Figure 7 C. After 8 weeks of implantation, the CSH-AuNCs-CIITP group showed a large amount of dense and complete cartilage tissue, which was rich in mature chondrocytes, and the results were better than those of the Col-AuNCs-CIITP, AuNCs-CIITP, AuNCs and Blank groups. H&E staining results showed that CSH-AuNCs-CIITP hydrogel could significantly promote the regeneration of cartilage tissue.
[0120] (3) The fixed samples were decalcified in 10% ethylenediaminetetraacetic acid (EDTA) solution for 7 days, then dehydrated in alcohol gradient, embedded in paraffin, cut into 6 μm slices, and finally the tissue sections were Masson stained.
[0121] The experimental results are as follows Figure 7 D. Eight weeks after surgery, the CSH-AuNCs-CIITP group had obvious blue staining compared with the Col-AuNCs-CIITP, AuNCs-CIITP, AuNCs, and Blank groups, indicating the generation of a large number of dense collagen fibers. The Masson results showed that the CSH-AuNCs-CIITP hydrogel could effectively promote the deposition of collagen.
[0122] (4) The fixed samples were decalcified in 10% ethylenediaminetetraacetic acid (EDTA) solution for 7 days, then dehydrated in alcohol gradient, embedded in paraffin, cut into 6 μm slices, and finally the tissue sections were stained with Saf-O / FG.
[0123] The experimental results are as follows Figure 7E. Eight weeks after surgery, Saf-O / FG staining of the CSH-AuNCs-CIITP group showed obvious rose red staining, indicating that a large amount of proteoglycan was secreted. The Saf-O / FG results showed that CSH-AuNCs-CIITP hydrogel could significantly promote the secretion of proteoglycan.
[0124] Example 14 Sirius red staining of CSH-AuNCs-CIITP
[0125] The collected specimens were fixed in 4% formaldehyde for 2 days and then decalcified in 10% ethylenediaminetetraacetic acid (EDTA) solution for 7 days. Subsequently, the samples were dehydrated in alcohol gradients, embedded in paraffin, and cut into 6 μm slices. Finally, the tissue sections were stained with Sirius red staining solution and images were acquired using a polarizing microscope.
[0126] The results of Sirius red staining are as follows Figure 8 AC. After 8 weeks of implantation, the staining images of the CSH-AuNCs-CIITP and Col-AuNCs-CIITP groups showed that collagen fibers were significantly distributed in the surface and basal regions, but there was no significant difference among the AuNCs-CIITP, AuNCs, and Blank groups. The orientation analysis of the regenerated collagen fibers in the CSH-AuNCs-CIITP group showed that the orientation of the surface region was mainly between -20° and 20°, accounting for 67.16% of all orientations, which was significantly higher than that of the Col-AuNCs-CIITP (58.66%), AuNCs-CIITP (47.48%), AuNCs (40.10%), and Blank (24.32%) groups. In the basal region, the collagen fibers of the CSH-AuNCs-CIITP group were mainly distributed in the range of 60°-90°, with a proportion as high as 69.54%, while the proportions of the Col-AuNCs-CIITP, AuNCs-CIITP, AuNCs and Blank groups were relatively low, at 61.26%, 49.42%, 44.56% and 43.07%, respectively. The results of picrosirius red staining showed that the CSH-AuNCs-CIITP hydrogel significantly promoted the orderly arrangement of collagen fibers in the regenerated cartilage tissue.
[0127] In summary, the present invention provides a collagen hydrogel loaded with gold nanoclusters, a preparation method and an application thereof; the hydrogel is mainly composed of gold nanoclusters functionalized with type II collagen targeting polypeptide (AuNCs-CIITP) and a thiol-crosslinked collagen (CSH) hydrogel carrier; the hydrogel has good physical and chemical properties, including a minimum swelling ratio, significant resistance to enzyme degradation, good injectability and enhanced mechanical properties; it has excellent biocompatibility and bioactivity, and can effectively promote cell proliferation, adhesion and cartilage differentiation; the hydrogel can intelligently respond to high levels of ROS, achieve controllable release of AuNCs-CIITP in CSH hydrogel, thereby targeting cartilage tissue, and has anti-inflammatory effects and cartilage regeneration ability; the hydrogel can significantly promote the repair of cartilage defects and can be used for the treatment of osteoarthritis in clinic.
Claims
1. A collagen hydrogel loaded with gold nanoclusters, characterized in that: The hydrogel is collagen encapsulating gold nanoclusters, and the gold nanoclusters are connected with targeting polypeptides.
2. The collagen hydrogel loaded with gold nanoclusters according to claim 1, characterized in that: The collagen is yak collagen.
3. The collagen hydrogel loaded with gold nanoclusters as claimed in claim 2, characterized in that: The yak collagen is thiol-modified yak type I collagen, type II and / or type III collagen.
4. The collagen hydrogel loaded with gold nanoclusters according to claim 1, characterized in that: The targeting polypeptide is type II collagen targeting polypeptide.
5. The method for preparing the collagen hydrogel loaded with gold nanoclusters according to any one of claims 1 to 4, characterized in that: The steps include: (1) At room temperature, a tetrachloroauric acid tetrahydrate solution, a targeting polypeptide aqueous solution and a glutathione solution are mixed, stirred evenly at 25° C., heated to 70° C., and stirred continuously in a dark environment; 75% ethanol is added for purification, centrifuged, and dried to obtain gold nanoclusters functionalized with the targeting polypeptide; (2) Dissolving collagen in acetic acid solution and adjusting the pH to 8.0; adding PBS buffer solution, EDTA and DL-N-acetylhomocysteine thiolactone; stirring at room temperature under nitrogen protection, adding dihexathreitol, continuing stirring, dialyzing, freeze-drying, dissolving in acetic acid solution, stirring, and dialyzing to neutrality to obtain thiol-modified collagen; (3) The gold nanoclusters functionalized with the targeted polypeptide obtained in step (1) and the thiol-modified collagen obtained in step (2) are quickly mixed at a mass ratio of 1:9 and placed at room temperature to form a collagen hydrogel loaded with gold nanoclusters.
6. The preparation method according to claim 5, characterized in that: The volume ratio of the targeting polypeptide aqueous solution to the glutathione solution in step (1) is 1:
9.
7. Use of the collagen hydrogel loaded with gold nanoclusters as claimed in any one of claims 1 to 4 in the preparation of products promoting bone / cartilage tissue regeneration.
8. Use of the collagen hydrogel loaded with gold nanoclusters as claimed in any one of claims 1 to 4 in the preparation of drugs for preventing and / or treating cartilage defects and arthritis.
9. The use according to claim 8, characterized in that The arthritis is infectious arthritis and / or non-infectious arthritis.
10. The use according to claim 9, characterized in that The non-infectious arthritis includes one or more of degenerative arthritis, rheumatoid arthritis, gouty arthritis and osteoarthritis.